Miocene transpression effects at the boundary of Central Carpathian Paleogene Basin and Pieniny Klippen Belt: examples from Polish-Slovakian borderland - Ludwiniak, Miroslaw (Geology, Geophysics and Environment, 2018)
A geological structural study has been conducted along the tectonic contact zone of the Central Carpathian Paleogene Basin (CCPB) and Pieniny Klippen Belt (PKB) in the eastern Podhale and western Spišska Magura areas. It concerned mostly the Central Carpathian Paleogene flysch strata and, to a lesser degree, the Upper Cretaceous rocks of the PKB. Tectonic deformation structures genetically related to the important tectonic boundary in question occur within a c. 1.5–2 km-wide strip of the Paleogene flysch rocks adjacent from the south to the PKB. Two parallel structural domains have been distinguished within this strip: the contact zone proper in the north and the peri-Pieniny monocline in the south. Most of the minor faults documented in the Paleogene flysch bear a record of dextral motion parallel to the contact zone. Some dextral-reverse oblique slip faults of NE-SW and W-E trends have also been recognized. Discrepancies in the orientation and sense of movement on strike-slip faults in the Paleogene flysch rocks and those in marlstones of the “klippen envelope” of the PKB were encountered. They probably reflect differences in the structural history of both the adjacent rock complexes, as the Upper Cretaceous deposits of the PKB must have experienced more deformation events and, in general, were affected by much more intense strain than those of the CCPB. Contractional structures, such as south-vergent reverse faults and recumbent folds which point to ca N-S tectonic shortening, have also been found in the Paleogene rocks. The entirety of the structural features found in the CCPB is characteristic of a transpressional regime. The regionally consistent coexistence of structures resulting from strike-slip movements and tectonic shortening, as well as features pointing directly to a transpressional regime, prove the transpressional dextral nature of the contact between the CCPB and PKB.